Membangun Komitmen untuk Sukses: Studi Kasus pada Koperasi Petani Bunga di Kopeng Kabupaten Semarang - Sundari, Pipit; Natoil, Natoil (LPPM Institut Pendidikan Nusantara Global, 2024)
Human resource management and cooperatives are very important for sustainability and performance in an era of globalization and increasingly fierce economic competition. This study investigates flower farmer cooperatives in Kopeng, Semarang Regency, and focuses on appropriate management methods to increase member commitment, which impacts the success and competitiveness of the cooperative. This research found a lack of knowledge about the components that influence member commitment and how to increase it. This research found that social factors, such as relationships between members, and economic factors, such as financial benefits, have a large influence on member commitment. The research results show that strengthening social relationships and providing financial incentives are effective management strategies to increase member commitment. The research results show that two effective management approaches to increase member commitment are improving social relationships and providing financial incentives. In addition, it was found that increased communication and participation in decision making were important components in increasing member commitment. This research offers theoretical and practical insights into managing member commitment in the context of flower farmer cooperatives and provides recommendations for cooperative practitioners and academics about management strategies that can be implemented to increase member commitment, which in turn will improve cooperative performance and sustainability.